Seroprevalance of selected bacterial and viral diseases of small ruminants in Terengganu, Malaysia - Abdirahman, Hashi Hamza (2020)
Small ruminant production is an important economic activity for many smallholder farmers in Malaysia. In the past decade, there has been increased demand for sheep and goat products. However, the development of regional livestock meat and milk trade is threated by the continuous threat of many infectious diseases of bacterial and viral origin, which limits the productivity of smallholder flocks. This study investigated the seroprevalence and risk factors of selected bacterial and viral diseases of sheep and goats in Terengganu, Malaysia. A cross-section survey was conducted to collect blood samples and farm management data from the selected farms January and December 2018. Blood samples were collected from 180 sheep (n=60) and goats (n=120) from 8 smallholder farms in Terengganu. A structured questionnaire was completed by individual farmers to furnish management data for the analysis of possible risk factors associated with seropositivity to bacterial and viral diseases. In the laboratory, serum was separated from coagulated blood by centrifugation and preserved for specific ELISA assays at -20 0C. Seroprevalence of SBV was determined using commercial ID Vet® SBV multispecies cELISA test. Detection of anti-CAEV antibodies was done using Qayee-Bio caprine arthritis encephalitis virus (CAE) sandwich-ELISA test kit with a sensitivity of 100% and specificity of 99.6%. A commercial Sandwich-ELISA kit (Sunlong) with a sensitivity of 100% and a specificity of 99.6% was used for the direct detection of specific antibody against Coxiella burnetii, bluetongue and contagious ecthyma virus. Standard Agar gel precipitation test (AGPT) was used for the detection of antibodies against Corynebacterium pseudotuberculosis. The Rose Bengal rapid plate agglutination test was used for the detection of Brucella antibodies. The optical densities (OD) of the tests were measured at 450nm using ELISA Microplate Reader (Tecan Sunrise®, Switzerland) and the percentage inhibitions calculated as 100 x [1- (Sample optical density/Negative control OD)] were interpreted as follows: OD values ≥ 40% = positive, OD values ≤ 30% = negative and OD values 30%-40% = doubtful. The result of serological tests indicates 10.6% (95% CI=6.6-16.7) overall seroprevalence of SBV with different (p<0.05) rates of infection between flocks, species, breed, gender, age, production system and management of small ruminants. The male had 5.26 times higher risk of exposure to SBV than females and young animals had 4.1 times higher risk of infection than adults. Serological analysis also revealed 27.2% (95% CI=22.8- 37.3) overall prevalence of contagious ecthyma with different (p<0.05) rates of infection among the flocks, species, breed, gender, production, and management of small ruminants. The goats had 3.1 times more risk of orf infection than sheep while dairy animals had 2.82 times higher odds of orf than the mean and mixed production. The overall seroprevalence of q fever was 16.7% (95% CI=12.3-24.5) with different (p<0.05) rates of infection among flocks, species, breed, age, production, and management system of small ruminants. The species sheep (OR=21.36; 95% CI=2.29- 198.41; p=0.007), especially Barbados black belly (OR=24.35; 95% CI=2.77-213.76; p=0.004) and Dorper sheep (OR=12.88; 95% CI=1.29-128.59; p=0.029), and the young age (OR=5.04; 95% CI=1.66-15.31; p=0.004) were risk the factors of q fever among small ruminants in the study area. The study further revealed 18.3% (95% CI=13.9-26.6) overall seroprevalence of bluetongue with different rates of infection among the flocks and breed of small ruminants. Flocks D (OR=5.29; 95% CI=1.16- 24.08; p=0.031), E (OR=8.22; 95% CI=1.46-46.27, p=0.017) and G (OR=18.50; 95% CI=2.17-16.46; p=0.008) were associated with higher risk of bluetongue in the study area. This study has also revealed 7.2% (95% CI=3.67-12.32) overall seroprevalence of CAEV with no difference (p>0.05) in infection rates among various categories of small ruminants. Our results also showed 5.6% (95% CI=2.3-10.0) overall seroprevalence of CLA with no difference (p>0.05) in infection rates among different categories of small ruminants. Serum antibodies against brucellosis were not detected in this study. This study reports the first occurrence of the novel and emerging transboundary Schmallenberg virus disease in Malaysia. The presence of anti-SBV antibodies in Malaysia indicates the potential effects of disease on small ruminant productivity. This study also revealed an alarming rate of re-emerging bluetongue and zoonotic q fever infections which need to be kept under control through a one health approach. We have also seen a high level of circulating antibodies to orf virus infection among the small ruminant population with a potential to cause a negative impact towards production. The absence of anti-brucella antibodies in small ruminants indicates the effectiveness of current control measures. In conclusion, this study highlights current seroprevalence status of selected bacterial and viral diseases of small ruminant in East Coast Malaysia and reports the first occurrence of novel and emerging SBV and also detected existing threats of re-emerging and zoonotic diseases, which requires a holistic herd health program and biosecurity implementation for effective control and prevention.